Is diet the key to longevity? - A narrative review of the dietary patterns of the Blue Zones - Drouliskou, Vasiliki-Fanouria; Poulianou, Eleni; Spyrakou, Efthymia (Magyar Gerontológia, 2023)
The purpose of this review was to gather the current literature concerning the relationship between longevity and the local nutrition patterns in the Blue Zones.